1994
DOI: 10.1007/bf00002570
|View full text |Cite
|
Sign up to set email alerts
|

A three-year study of controls on methane emissions from two Michigan peatlands

Abstract: Abstract. We investigate temporal changes in methane emissions over a three-year period from two peatlands in Michigan. Mean daily fluxes ranged from 0.6-68.4 mg CH4 mm2 d-' in plant communities dominated by Chamaedaphnecalyculata, an ericaceous shrub, to 11 S-209 mg CH4 m-* d-' in areas dominated by plants with aerenchymatous tissues, such as Carex oligosperma and Scheuchzeria palustris. Correlations between methane flux and water table position were significant at all sites for one annual cycle when water ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
133
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(155 citation statements)
references
References 31 publications
21
133
0
1
Order By: Relevance
“…The temporal response in CH 4 emissions to variations in temperature is consistent with previous studies (Frolking and Crill, 1994;Shannon and White, 1994;Laine et al, 2007) Net CH 4 flux is dependent on the balance between oxidation and production processes. As the temperature response in methanogens is generally greater than that of methanotrophs (Segers, 1998), the overall effect on net emissions is positive.…”
Section: Drivers Of Temporal Variation (Site 2)supporting
confidence: 90%
See 1 more Smart Citation
“…The temporal response in CH 4 emissions to variations in temperature is consistent with previous studies (Frolking and Crill, 1994;Shannon and White, 1994;Laine et al, 2007) Net CH 4 flux is dependent on the balance between oxidation and production processes. As the temperature response in methanogens is generally greater than that of methanotrophs (Segers, 1998), the overall effect on net emissions is positive.…”
Section: Drivers Of Temporal Variation (Site 2)supporting
confidence: 90%
“…Although significant changes in water table depth (e.g. drainage or drain blocking) have repeatedly been shown to strongly influence CH 4 emissions Strack et al, 2004), a much weaker relationship is often observed with temporal water table variability in the field (Frolking and Crill, 1994;Shannon and White, 1994). In our study water table was a significant correlate only in the Hollow chambers, although soil moisture, which may provide a better measure of both current The drivers of temporal variability were not consistent across the study site.…”
Section: Drivers Of Temporal Variation (Site 2)mentioning
confidence: 99%
“…This is either due to the longer acclimation periods that methanogenesis requires or suppression of methanogenesis from the mobilisation of sulphate during the more aerobic conditions present when the water level fell (Gauci et al, 2004). In fact, periodic lowering of the water table to 0.15-0.20 m below the surface (within the range observed here ; table 3) has been demonstrated to completely inhibit CH4 generation (Shannon and White, 1994;Altor and Mitsch, 2006). Therefore, weed cutting may have potential as a management tool to mitigate greenhouse gas emissions from riparian wetlands.…”
Section: Perspective On Mitigating Green House Gas Emissionsmentioning
confidence: 54%
“…Dise et al, 1993;Shannon and White, 1994;Roslev and King, 1996). This is not surprising as the oxygen availability and hence potential for aerobic degradation of organic matter and CH 4 oxidation increase when the water table is lowered.…”
Section: Discussionmentioning
confidence: 95%
“…Enhancement occurs through production and release of organic matter (Holzapfel-Pschorn et al, 1986;Schütz et al, 1991), and by transportation of CH 4 via molecular diffusion or convective flow through the internal gas spaces of the plants, thus bypassing oxidation in the anoxic/oxic interface (Shannon and White, 1994;Sorrell and Boon, 1994;Shannon et al, 1996). Many species of emergent macrophytes possess a convective flow mechanism which is many times more efficient in transporting gases than diffusion alone (Brix et al, 1992), and hence these species may accelerate the emission of CH 4 from wetlands (Brix et al, 1996).…”
Section: Introductionmentioning
confidence: 99%